Study On RF Signal Propagation In An Indoor Environment For Wireless Communication Applications - Teh , Chin Hui (2001)
This dissertation presents an improved variant of ray tracing technique, which we term as ray-polygon tracing, for propagation modelling. Generic polygons are used to represent the infinite number of rays(high frequency signals) emitted. The ray-polygons are clipped by obstacles, as they propagate away from the transmitter. In the mean time, new reflected and transmitted ray-polygons and images are created.